Geoarchaeology of the Cobrinhos site (Vila Velha de Ródão, Portugal) - a record of the earliest Mousterian in western Iberia. (April 2019) - Pereira, Telmo; Cunha, Pedro P.; Martins, António A.; Nora, David; Paixão, Eduardo; Figueiredo, Olívia; Raposo, Luis; Henriques, Francisco; Caninas, João; Moura, Delminda; Bridgland, David R.
Abstract: Cobrinhos (Vila Velha do Ródão, central eastern Portugal) is a Mousterian site found during factory construction in 2014. This area is located in the Lower Tejo valley, which is characterized in terms of geomorphology by six river terraces, numbered downwards (T1 to T6), with Palaeolithic industries associated only with T4 to T6. Terrace T4 was recently dated as spanning ca. 340 ka to 155 ka, with Acheulean in the basal and middle levels and early Mousterian in the uppermost levels. The geological context at Cobrinhos is a colluvial unit that links to the top of T4. It has evidence for palaeoweathering with the same characteristics as seen in T1 to T4, considerably different from that seen in T5 and T6. Despite disturbance by ploughing, the site shows a uniform distribution of sizes and shapes of lithic artefacts, with thousands of implements <30 mm and a coherent Mousterian assemblage including Levallois and discoidal reduction pieces, Levallois flakes, blades and points, pseudo-Levallois points, notches, denticulates, sidescrapers, and an absence of Acheulean or Upper Palaeolithic tools. The available data suggest that the colluvial unit is coeval with the topmost T4 deposits and that the Cobrinhos industry is in its original geomorphological context. Although the colluvial unit cannot be dated directly, from the combination of site data and available published luminescence ages for T4, we suggest a probable age of ca. 165 to 155 ka for this industry. These results are of relevance in the investigation of the demise of archaic Pleistocene human populations and the proliferation of Neanderthal groups in Iberia. Highlights: Cobrinhos is a new open-air Middle Palaeolithic site associated with the Tejo River terrace staircase. Being in a colluvial context, it is impossible to date directly. The combination of archaeology and geo-disciplines allows reliable deduction of ages at ca. 165–155 ka. The variety of artefacts, their sizes and the many small artefacts show context reliability. Lithic analysis confirms a coherent Mousterian assemblage.